Kementerian-kementerian, jabatan, dan agensi di Malaysia (Kuala Lumpur Jabatan Penerangan Malaysia, 2005)
Organizational purposes and functions of the executive departments and administrative agencies in Malaysia.
Errata slip tipped in at end.
Keywords: Administrative agencies -- Malaysia